Highly Illogical Behavior - Whaley, John Corey (New York Dial Books, 2016)
Agoraphobic sixteen-year-old Solomon has not left his house in three years, but Lisa is determined to change that--and to write a scholarship-winning essay based on the results.
103923
Keywords: Agoraphobia -- Juvenile fiction; Panic attacks -- Juvenile fiction; Friendship -- Juvenile fiction; Gays -- Juvenile fiction; Young adult fiction